Recent progress in metal oxide-based electrode materials for safe and sustainable variants of supercapacitors - Asghar, Ali; Khan, Karim; Hakami, Othman; Alamier, Waleed M.; Ali, Syed Kashif; Zelai, Taharh; Rashid, Muhammad Shahid; Tareen, Ayesha Khan; Al-Harthi, Enaam A. (Frontiers in Chemistry, 2024)
A significant amount of energy can be produced using renewable energy sources, however storing massive amounts of energy poses a substantial obstacle to energy production. The economic crisis has led to rapid developments in electrochemical energy storage devices (EESDs), especially rechargeable batteries, fuel cells and supercapacitors (SCs), which are effective for energy storage systems. Researchers have lately suggested that the among the various EESDs, SC is an effective alternate for energy storage due to the presence of following characteristics such as SCs offer high-power density, improvable energy density, fast charging/discharging, and good cyclic stability. This review highlighted and analysis the concepts of supercapacitor, types of super capacitors on the basis of electrode materials, highlight the several feasible synthesis processes for the preparation of metal oxide (MOs) nanoparticles and discussed the morphological effects of MOs on the electrochemical performance of the devices. In this review we generally focusing on the pseudo capacitors SCs which mainly contains MOs and their composites materials, and also highlight their future possibilities; so long as a useful application of MOs based materials in supercapacitors. The novelty of MO's electrode materials is primarily due to the presence of synergistic effects in the hybrid materials, rich redox activity, excellent conductivity, and the chemical stability, which makes them excellent for SCs applications.